Is it Safe for Me to Fly? - Brooker, Peter (Royal Statistical Society, 2008)
‘Is it Safe for Me to Fly’ seems like a simple question. But who is Me, what is Safe, and why is there a reason for focusing on Fly? Is the underlying question: ‘Are the people responsible doing everything they should to make flying safe?’ Good questions – so what are the answers?